Immune recovery folliculitis: Case reports in HIV naïve and experienced patients. (2021) - Camici, Marta; Scarabello, Alessandra; Del Nonno, Franca; Colombo, Daniele; Gagliardini, Roberta; Antinori, Andrea
Abstract: Immune recovery folliculitis (IRF) is defined as the development of an inflammatory disorder of the facial pilo-sebaceous unit due to the immune reconstitution inflammatory syndrome (IRIS). Skin lesions can be related to an immune response against skin saprophyte bacteria (e.g. Demodex folliculorum, Cutibacterium acnes). The rapid reconstitution of T lymphocyte, with a CD8+ predominance, is considered a key pathogenic factor for this phenomenon. IRF is clinically similar to acne vulgaris and can be challenging to treat. Patients with facial pustules can experience social discomfort. Here we report two cases of IRF diagnosed at the human immunodeficiency virus (HIV) clinic of the National Institute of Infectious Diseases L. Spallanzani, in Rome, Italy. The first case occurred in an antiretroviral therapy (ART)-experienced patient, after a treatment simplification; the second one was registered in an ART-naïve patient, diagnosed with acute HIV infection shortly, after ART initiation. To date, an IRF secondary to an ART switch, has not been described yet. IRF should be ruled out and considered in differential diagnosis from antiretroviral drug-related skin effects.